CS exposure--clinical effects and management. Issue 3 (1st May 1999) - Worthington, E; Nee, P A
Abstract : The number of people exposed to CS spray presenting to accident and emergency departments is on the increase. Its effects, though usually minor and short lived, involve several systems and can occasionally be life threatening. It is therefore important that staff are able to manage these patients and know when and how to protect themselves and others from further contamination.